(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يتناول البحث تقييم إجراءات التسويق الداخلي في شركات الوساطة المالية العاملة في مدينة دمشق من خلال تقييم وجود ثلاثة إجراءات من إجراءات التسويق الداخلي في هذه الشركات وهي (ثقافة الخدمة، التدريب الداخلي، نشر المعلومات التسويقية على العاملين). اعتمد البحث على المنهج الكمي والفلسفة الوضعية والمدخل المنهجي الاستنتاجي كأسلوب للدراسة من خلال تحويل النظرية التي تتحدث عن تطبيق التسويق الداخلي في شركات الوساطة المالية إلى فرضيات محددة قابلة للاختبار. وشمل مجتمع البحث كل العاملين في شركات الوساطة المالية العاملة في مدينة دمشق، حيث تم توزيع (95) استبانة على العاملين في شركات الوساطة المالية، أعيد منها (80) استبانة بنسبة استجابة بلغت (84.21%)، وباستخدام الأساليب الإحصائية المناسبة تم التوصل إلى النتائج الآتية: 1_ توجد ثقافة خدمة لدى شركات الوساطة المالية العاملة ضمن مدينة دمشق. 2_ لا يوجد تدريب داخلي لدى شركات الوساطة المالية العاملة ضمن مدينة دمشق. 3_ تقوم شركات الوساطة المالية العاملة في مدينة دمشق بنشر المعلومات التسويقية للعاملين فيها. 4_ لا توجد فروق ذات دلالة إحصائية بين متوسطات تقييمات العاملين في شركات الوساطة المالية للتدريب الداخلي بحسب عدد سنوات الخبرة، بينما توجد فروق ذات دلالة إحصائية بين متوسطات تقييمات العاملين في شركات الوساطة المالية لثقافة الخدمة ولنشر المعلومات التسويقية بحسب عدد سنوات الخبرة. This paper aims to evaluate internal marketing practices (the service culture, the internal training and disseminate the marketing information to employees) in all brokerage firms in Damascus. The research adopted quantitative approach and positivism philosophy besides deductive approach as scientific methodology for the research. The research population included employees working in all brokerage firms, (95) questionnaires were distributed to the workers in brokerage firms, (80) questionnaires were responded, the response rate was (84.21%). By using appropriate statistical methods, the study reached the following results: 1. There is service culture within brokerage firms working in Damascus. 2. There is no internal marketing within brokerage firms working in Damascus. 3. All brokerage firms in Damascus disseminated the marketing information to employees. 4.There were no statistically significant differences between the averages of employees’ evaluation of internal training in brokerage firms according to the number of experience years, while there were statistically significant differences between the averages of employees’ evaluation of service culture and disseminate the marketing information to employees in brokerage firms according to the number of experience years.